2016
DOI: 10.1007/s10964-016-0577-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationships between Bullying and Moral Disengagement among Adolescents

Abstract: Moral disengagement is a series of cognitive processes used to disengage moral standards to achieve absolved guilt and permit immoral conduct and has been found to be an important connection to bullying and aggressive behaviors among adolescents. This study examined the longitudinal relationship between moral disengagement and bullying behavior among a group of adolescents from fifth grade to ninth grade (n = 1180, mean age = 12.2, SD = 1.29, 46.5 % female, 80.2 % Caucasian/White, 7.1 % Black/African American,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
53
0
23

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 48 publications
12
53
0
23
Order By: Relevance
“…However, bullying was analyzed as a distal outcome and bullying trajectories were not reported. Another longitudinal study reported that moral disengagement was a predictor of bullying perpetration after several months (Wang, Ryoo, Swearer, Turner, & Goldberg, ). Future studies should discover predictors of the transition patterns discovered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, bullying was analyzed as a distal outcome and bullying trajectories were not reported. Another longitudinal study reported that moral disengagement was a predictor of bullying perpetration after several months (Wang, Ryoo, Swearer, Turner, & Goldberg, ). Future studies should discover predictors of the transition patterns discovered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering attrition, the perspectives of youths with more significant behavioral and emotional risk were missing. Other studies struggle with retaining the most at-risk youth in longitudinal research (e.g., Wang, Ryoo, Swearer, Turner, & Goldberg, 2017). All participants were recruited from the same school in Grade 8, and results may be affected by school-specific factors not measured in this study.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…First, all the constructs are evaluated through self-report measures that may be subject to social desirability bias. Indeed, referring to the tendency to make self-serving CDs and to involvement in bullying behaviors, it is known (e.g., [95]) that adolescents are more careful about their social image than other age groups, and may be unlikely to report behavior that displays them in a negative light. Furthermore, regarding exposure to community violence, a more objective and comprehensive description of violence in the everyday lives of adolescents, including official data from national census agencies and police departments, may provide a more complete assessment of exposure to violence [96].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%